Trace elements, rare earth elements and scandium concentration in a weathering profile of metaultramafic rock (Bom Jesus da Penha, Minas Gerais, Brazil) - Faria Júnior, Ilio Rodarte; Luvizotto, George Luiz; Rosolen, Vania Silvia (Geologia USP. Série Científica, 2018)
The development of lateritic horizons is responsible for chemical and mineralogical reorganization in the parent rock. The final arrangement is controlled by the primary composition of the parent material, climate conditions, the presence of living organisms, topography, and time. This work presents chemical data on two weathering horizons developed from chlorite-amphibole schist. The upper horizon is composed of a red clayey kaolinitic soil. A green saprolitic horizon with ocher plinthite and neoformed montmorillonite occurs below it. Concentrations of analyzed elements vary along the soil profile and all of the metals have peak concentrations that are 100% higher than the parent rock. The upper part of the soil profile is enriched with Al2O3, U, Th, Zr and TiO2 as well as with kaolinite and iron oxide-hydroxides. The highest concentrations of Fe2O3, V and Co occur in the transition zone between the soil and saprolite horizons. On the other hand, the highest values of Mn, Cr2O3, Ni, Zn, Cu and Rare Earth Elements occur in the montmorillonite-bearing saprolite horizon. CaO, MgO and SiO2 are depleted along the profile. Considering the metaultramafic composition of the parent rock, we highlight the notable enrichment of rare earth elements, yttrium and scandium in the weathering profile, which can be compared to the lateritic mineralization models of these elements.